Effect of Maillard reaction on the structural and immunological properties of recombinant silver carp parvalbumin. (January 2017) - Zhao, Yong-Juan; Cai, Qiu-Feng; Jin, Teng-chuan; Zhang, Ling-Jing; Fei, Dan-Xia; Liu, Guang-Ming; Cao, Min-Jie
Abstract: The purpose of this study was to investigate the influence of Maillard reaction on the structural and immunological properties of parvalbumin (PV), the major allergen in fish. Recombinant silver carp PV (rPV) was employed and incubated with glucose at 60 °C for 72 h. The IgG/IgE binding properties of rPV were weakened after Maillard reaction as demonstrated by dot blotting. Allergenicity decrease of rPV by Maillard reaction was further confirmed on sensitized RBL-2H3 cell with the decreasing release of β-hexosaminidase, histamine and suppressing the production of interleukin-4 (IL-4) and tumor necrosis factor-α (TNF-α). Comparison of the glycation sites with documented epitopes suggested the direct blocking of conjugated carbohydrates (K88, K97, and K108 ) on IgE-binding epitopes. Glycated rPV (G-rPV) exhibited slightly more resistance against pepsin digestion in vitro, which probably due to the formation of aggregation and the increase of hydrophobicity of G-rPV. Highlights: Maillard reaction reduces immunoreactivity of recombinant parvalbumin (rPV). Six glycation sites of glycated rPV were modified (K46, K55, K84, K88, K97 and K108 ). Three of six glycation sites (K88, K97, and K108 ) located on IgE-binding epitopes. Maillard reaction promoted aggregation formation of glycated rPV. Maillard reaction increased surface hydrophobicity of glycated rPV.